2012
DOI: 10.3945/jn.112.162198
|View full text |Cite
|
Sign up to set email alerts
|

Behavior and Monoamine Deficits in Prenatal and Perinatal Iron Deficiency Are Not Corrected by Early Postnatal Moderate-Iron or High-Iron Diets in Rats,

Abstract: Developmental iron deficiency anemia (IDA) causes brain and behavioral deficits in rodent models, which cannot be reversed when treated at periods equivalent to later infancy in humans. This study sought to determine whether earlier iron treatment can normalize deficits of IDA in rats and what iron dose is optimal. The offspring of dams with IDA during gestation were cross-fostered at postnatal d (P) 8 to dams receiving diets with 1 of 3 iron concentrations until weaning (P21): 0.003-0.01 g/kg [totally iron de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
74
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 70 publications
(80 citation statements)
references
References 43 publications
4
74
2
Order By: Relevance
“…56 One curiosity among the literature is why lower levels of iron fortification that more closely resemble the levels in breast milk have not been included in clinical studies of the possible health benefits of iron supplementation, particularly when some evidence suggests that moderate iron supplementation is sufficient (and even preferable) for the correction of behavioural deficits that arise from iron deficiency. 57 If, as the ESPGHAN reported, iron fortification is only beneficial to infants who are preterm and have anaemia, the lack of acute health effects that arise from overexposure to iron should not exclude modest supplementation from further study. We believe that a priority in paediatric research is the rigorous determination of iron supplementation needs of infants according to their individual iron status.…”
Section: Box 2 | Evolution Of Iron Regulatory Mechanismsmentioning
confidence: 96%
“…56 One curiosity among the literature is why lower levels of iron fortification that more closely resemble the levels in breast milk have not been included in clinical studies of the possible health benefits of iron supplementation, particularly when some evidence suggests that moderate iron supplementation is sufficient (and even preferable) for the correction of behavioural deficits that arise from iron deficiency. 57 If, as the ESPGHAN reported, iron fortification is only beneficial to infants who are preterm and have anaemia, the lack of acute health effects that arise from overexposure to iron should not exclude modest supplementation from further study. We believe that a priority in paediatric research is the rigorous determination of iron supplementation needs of infants according to their individual iron status.…”
Section: Box 2 | Evolution Of Iron Regulatory Mechanismsmentioning
confidence: 96%
“…Previous studies in humans and animal models of fetal and early postnatal life iron deficiency demonstrate long-lasting impairments in learning and memory and socio-emotional behaviors (18,20,35,60,71), as well as increased risk for depression and schizophrenia (27,37). The long-term biobehavioral deficits occur despite treatment with iron and have been ascribed in part to persistence of abnormalities in monoamine signaling, myelination, neural metabolism, and expression of neuroplasticity-associated proteins into adulthood ( systematically analyzing the long-term effect of early-life iron deficiency specifically on proteins expressed in adult hippocampal synapses and addresses the persistent defect of learning and memory and sensory-motor gating.…”
Section: Discussionmentioning
confidence: 99%
“…These deficits have been replicated in rodent models of fetal-neonatal iron deficiency (35). Of relevance to the present study, hippocampal-dependent learning and memory as well as prepulse inhibition, an index of sensory-motor gating linked to the schizophrenia endophenotype, were abnormal in the rat model (10,20,35,53,67,71).…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Most of these experiments have used rodents, but more recently, studies in human subjects have shown that changes in the cognitive function of babies can be related to maternal iron status (4,21,22) .…”
Section: Consequences Of Deficiencymentioning
confidence: 99%